103k views
1 vote
May I have some help pls

May I have some help pls-example-1

2 Answers

1 vote

Answer:

y = -4

Explanation:

-3x - 9y = 36

if x = 0

-3x would have to equal 0

so 0 - 9y = 36

36 - 0 = 0

so 36 will have to divide by 9 which equals 4

and since it's 0 - 9y, the number will have to be negative. so it will be -4.

so 0 *-3x* - -36 *9y* = 36

= 0 + 36

= 36

User Hanin
by
5.1k points
2 votes

Answer:

y = 4

Explanation:

-3x - 9y =36

-9y = 36 + 3x

-9 = ( 36 + 3x ) ÷ 9

y = 4 + 3x

y = 4 + 3(0)

y = 4

User Teastburn
by
5.7k points